Exploring the effect of fluid management guided by optic nerve sheath diameter on postoperative headache in women with cesarean section - Qiao Yang; Ruiming Deng; Qiaoling Weng; Tingyu He; Ziqiang Dong; Xianwei Jin; Weibo Zhong (Scientific Reports)
Abstract In cesarean section surgery, spinal anesthesia can lead to a reduction in intracranial pressure (ICP), which may result in headaches. Adequate fluid replacement is generally required postoperatively to prevent low ICP. However, excessive empirical fluid replacement can increase the circulatory burden on the patient and potentially elevate ICP, thereby contributing to the occurrence of headaches. This trial aims to investigate whether fluid management guided by ultrasound measurement of the optic nerve sheath diameter can reduce the incidence of postoperative headaches in patients. This single-center randomized controlled clinical trial was conducted at Ganzhou People’s Hospital in China from December 2022 to July 2023. A total of 138 ASA II and III patients aged 18 years and older, scheduled for cesarean section under spinal anesthesia, were randomly assigned to either a restricted infusion group (Group E, n = 71), which underwent restrictive infusion adjustments to maintain the optic nerve sheath diameter within the normal range (2.2–5 mm), or an empirical infusion group (Group C, n = 67), where the optic nerve sheath diameter was solely monitored, and empirical infusion treatment was employed. Within 72 h post-operation, all patients were monitored every 12 h for ultrasound-measured optic nerve sheath diameter (ONSD) and the occurrence of postoperative headaches. The primary outcome was the incidence of postoperative headaches. Secondary outcomes included ONSD assessed by ultrasound, pain scores using the visual analog scale (VAS), postoperative fluid supplementation, nausea and vomiting, back pain, mean arterial pressure (MAP), heart rate (HR), length of hospital stay, and patient satisfaction. The incidence of postoperative headache in Group E was lower than that in Group C, however, this difference was not statistically significant (P = 0.094). There was no difference in the volume of fluid replacement between the two groups within the first 0–12 h post-surgery, but significant difference was observed between 12 and 24 h (P = 0.002). Additionally, there was no significant reduction in discharge time between two groups (P = 0.309). Under ultrasound guidance, maintaining a normal diameter of the optic nerve sheath does not decrease the incidence of postoperative headaches in women with cesarean section receiving a spinal anesthesia. However, it may offer patients a more effective approach to fluid replacement. Trial registration: ChiCTR.org.cn (ChiCTR2400089214). Date of registration: 4/9/2024.